Project evaluation: main characteristics - Moutinho, Nuno (2010)
The evaluation process of real investment projects must consider not only the traditional financial approach, but also non-financial aspects. Non financial analysis can provide additional relevant information about projects. We investigate financial and non-financial areas most relevant in project appraisal. We present main critical success factors and areas of analysis that lead to the perception of project success. Finally, companies are segmented to verify its financial and nonfinancial practices, considering industries, type of project, size and duration of the project. The results show that there are other factors in addition to financial that affect the investment decision with great importance, specifically the strategic, technical and commercial areas. Perceived success of a project is related to the consideration of strategic, political and human resources aspects in its evaluation. There is a greater perception of success when companies attach greater importance to financial and commercial aspects in project appraisal. The existence of many financial and strategic factors is associated with a greater perceived success of the project. We found that there is a greater perception of success in companies with larger projects, when the chairman of the board has higher tenure and when the project manager has higher degree and has variable reward.